Identifying motivational factors that influence youth participation in volunteerism: A pilot study on TFTN Pahang / Azniza Ahmad Zaini ...[et al.] - Ahmad Zaini, Azniza; Mustapha, Musramaini; Tajuddin, Norulhuda; Ishak, Maisarah; Hussin, Adibah (2013)
The involvement of young people nowadays in volunteering activities such as education, health and welfare, environmental concerns and services for youth group and senior citizens has been increasing in Malaysia. The outcomes of being involved in volunteering activities could produce a feeling of self-worth and respect. The existence of a group named Teach for The Needs (TFTN) in Malaysia has so far contributed a lotto the volunteering activities especially in giving free education services to the orphans and children from poor families. However, lack of research has been done to identify the motives that youth offer for their participation in volunteering activities. Hence, a pilot study on TFTN group has been carried out to investigate the motivational factors that influence the youth participation in volunteerism. Self-administered questionnaire were distributed to the members of TFTN group from Pahang state that were chosen as respondents for this pilot study. The result reveals that factors like values, satisfaction and social motivate the TFTN members to be involved in volunteering activities.